Pengaruh Promosi Penjualan, Iklan, dan E-WOM pada Pembelian Impulsif dengan Emosi Positif sebagai Variabel Moderasi (Survei Mahasiswa Pengguna Blibli di Kota Padang) - Uli, Ester Roma; Rino, Rino (Universitas Negeri Padang, 2024)
This research aimed to investigate consumer loyalty towards Blibli among students in Padang City, who were influenced by sales promotions, advertising, and electronic word-of-mouth (E-WOM), with positive emotions as a moderating variable. Type of this researcher is causal research design. The sampling technique is purposive sampling with a total sample 170, determined through Structural Equation Modeling (SEM). Primary data, collected through questionnaires distributed to students in Padang City who met the criteria of being currently enrolled and having made at least one purchase at Blibli, was utilized in this study. The analytical method used SEM (SmartPLS 4.0). The findings of the study are: 1) Sales promotions do not influence impulse buying at Blibli. 2) Advertising has a significant effect on impulse buying at Blibli. 3) E-WOM positively impacts impulse buying at Blibli. 4) Positive emotions can moderate the effect of sales promotions on impulse buying at Blibli. 5) Positive emotions can moderate the relationship between advertising and impulse buying at Blibli. 6) Positive emotions can moderate the relationship between E-WOM and impulse buying.